Study on the Influence of Processing Oil on the Physical Mechanical Properties and Adhesion of Ethylene Propylene Diene Monomer (EPDM) Rubbers to Polyester Fabrics - Liem, Nguyen Thanh; Linh, Nguyen Pham Duy; Tung, Nguyen Huy; Phuc, Bach Trong; Chuong, Bui; Thuy, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 2, 2020)
In this paper, the influence of paraffinic oil on the physical mechanical and thermal properties of three EPDM rubbers types Buna EP T.6465, Keltan 5260Q and Keltan 6160 D have been investigated. The results showed that the tensile strength and the elongation at break of Keltan 5260Q and Keltan 6160 D with 10 phr paraffinic oil represent the improvement of 57.8% to 57.6% and 71% to 81% respectively, compared to EPDM rubbers without paraffinic oil. The mean peel force of EPDM keltan 6260D with 10 phr paraffinic oil loaded is about 36% and 32.5% higher than that of keltan 5260Q and EP.T 6465 respectively. Beside that at the suitable paraffinic oil contents, the thermal resistance of Keltan 5260 Q and 6160D seems to be a little higher than that of without processing oil and these EPDM rubbers are suitable for application to high thermal resistance rubber products.